Specificities of SMEs relevant to knowledge management: a systematic literature review. (17th August 2020) - Sartori, Jeanfrank T.D.; Frederico, Guilherme F.; Freitas, Maria Do Carmo Duarte; Júnior, Ricardo Mendes
The various positive impacts that knowledge management (KM) offers to organisations that effectively apply it are fully consolidated in the literature. Nonetheless, even large enterprises, although usually abundant of human, financial and technological resources, are not always expressively successful on applying that concept. Small and medium-sized enterprises (SMEs) present numerous additional characteristics, challenges and obstacles to the implantation of KM. To contribute to change that reality, it is clear from the scientific perspective the importance of the effort to consolidate the state of art of knowledge on this field, especially because the last similar work dates to 2012 and significant research in different countries has been produced since then. In addition, just a few of previous works have their main goal like what is here presented. Thus, the present article is a systematic review of the literature of the relevant specificities of SMEs for KM in a global perspective.